Requirements Engineering: Foundation for Software Quality 16th International Working Conference, REFSQ 2010, Essen, Germany, June 30July 2, 2010. Proceedings - Wieringa, Roel.; Persson, Anne. (Lecture Notes in Computer Science, 2010)
This volume constitutes the refereed proceedings of the International Working Conference REFSQ 2010, held in Essen, Germany, in June/July 2010.